Mapping the Transcription and Replication Promoters of Respiratory Syncytial Virus - Fearns, Rachel (American Society for Microbiology, 2002)
An important, unresolved issue in mononegavirus biology is whether or not transcription is initiated by the same promoter as RNA replication. In this study, residues important for respiratory syncytial virus (RSV) transcription and RNA replication were identified by subjecting the first 26 nucleotides of genome RNA to saturation mutagenesis. This analysis was performed using a genome analog that allowed transcription and RNA replication to be dissociated from each other and monitored as independent events in an intracellular assay. This analysis showed that nucleotides 3C, 5C, 8U, 9U, 10U, and 11U were important for transcription and RNA replication. Additional nucleotides (1U, 2G, 6U, and 7U) were important for RNA replication, but not transcription. At position 4, G versus C or U augmented transcription and decreased replication, showing that the naturally occurring assignments in the genomic (4G) and antigenomic (4U) promoters are optimal for transcription and RNA replication, respectively. These data show that RSV transcription and RNA replication each involve a cis-acting signal at the very 3" end of the genome. This signal appears to contain a minimum, common element that functions in both transcription and RNA replication, defined by those substitutions that had similar effects on the two processes. Apart from these common nucleotides, other positions were involved in RNA replication but not transcription or had different effects on the two processes. This indicates that the promoters for transcription and replication involve overlapping sets of nucleotides at the very 3" end of the genome and provides evidence that the nucleotide preferences for the two processes are not identical.